2021
DOI: 10.1128/msystems.00820-20
|View full text |Cite
|
Sign up to set email alerts
|

Systems Biology behind Immunoprotection of Both Sheep and Goats after Sungri/96 PPRV Vaccination

Abstract: Immune response is a highly coordinated cascade involving all the subsets of peripheral blood mononuclear cells (PBMCs). In this study, RNA sequencing (RNA-Seq) analysis of PBMC subsets was done to delineate the systems biology behind immune protection of the vaccine in sheep and goats. The PBMC subsets studied were CD4+, CD8+, CD14+, CD21+, and CD335+ cells from day 0 and day 5 of sheep and goats vaccinated with Sungri/96 peste des petits ruminants virus. Assessment of the immune response processes enriched b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 67 publications
(80 reference statements)
2
16
0
Order By: Relevance
“…The upregulation of genes of the key immune molecules like ISG15 in all cell subsets and IFIT3, MX1, and ISG15 in certain cell subsets of the sheep PBMCs was found at earlier stages (5 dpv) of PPRV vaccination ( 11 ). In goats, the elevated levels of the genes of ISG20, ISG15, IRF7, various IFITs, MX1, and MX2 was found at 5 dpv ( 11 ). The altered expression of these PBMC proteins, identified following PPRV vaccination of sheep and goats, suggests marked changes in cellular signaling pathways to modulate host responses.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The upregulation of genes of the key immune molecules like ISG15 in all cell subsets and IFIT3, MX1, and ISG15 in certain cell subsets of the sheep PBMCs was found at earlier stages (5 dpv) of PPRV vaccination ( 11 ). In goats, the elevated levels of the genes of ISG20, ISG15, IRF7, various IFITs, MX1, and MX2 was found at 5 dpv ( 11 ). The altered expression of these PBMC proteins, identified following PPRV vaccination of sheep and goats, suggests marked changes in cellular signaling pathways to modulate host responses.…”
Section: Discussionmentioning
confidence: 98%
“…ISG15, IRF7, MX1, RSAD2, and IFIT3 have been found to play a vital role in modulating immune response against the viral infection (26-33). The upregulation of genes of the key immune molecules like ISG15 in all cell subsets and IFIT3, MX1, and ISG15 in certain cell subsets of the sheep PBMCs was found at earlier stages (5 dpv) of PPRV vaccination (11). In goats, the elevated levels of the genes of ISG20, ISG15, IRF7, various IFITs, MX1, and MX2 was found at 5 dpv (11).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…ISGs -ISG15, ISG20, IRF7, IFIT1, IFIT3, IFIT5, MX1, IFI6, and OAS1 whose antiviral activity has been reported in various RNA virus infections (Schneider, Chevillotte et al 2014), have also been found to be elevated in lymphocytes isolated from virulent PPRV infected goat (Wani, Sahu et al 2019) and various PBMCs subsets isolated from Sungri 96/PPRV vaccine goats (Wani, Praharaj et al 2021).…”
Section: Discussionmentioning
confidence: 90%
“…In earlier studies of host-PPRV interaction, we have reported higher expression of genes encoding different molecule species such as Interferon-Stimulated Genes (ISGs), interleukins and viral sensors involved in innate immunity following PPRV infection (Wani, Sahu et al 2019, Wani, Praharaj et al 2021). Among the immune-related processes enriched by the upregulated genes, we found that upregulated genes involved in these processes are ISGs like IFI44L, IFI6, IFIT1, IFIT2, IFIT3, IFIT5, IRF7, ISG15, ISG20, and MX1; interleukin and interleukin receptors such as IL17RA, IL18, IL1RN, IL4R, IL7R, IL10RB, IL17RB, IL1R2, IL1RL1, IL27, IL27RA, IL33, and IL6ST, and viral sensors like RIG-I (DDX58), MDA5 (IFIH1) and TLR2, TLR3, TLR4, and TLR6 (Figure 5E).…”
Section: Immune-related Genesmentioning
confidence: 99%